2003
DOI: 10.1002/cncr.11880
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tumor volume and surface area with lymph node status in patients with multifocal/multicentric breast carcinoma

Abstract: BACKGROUND Multicentric breast carcinomas have a higher frequency of axillary lymph node metastasis than unifocal tumors of similar stage. It remains unclear whether this merely reflects larger tumor volumes or a different biologic behavior. The authors have shown previously that when aggregate tumor diameter are used for staging, unifocal and multifocal tumors have a similar frequency of axillary lymph node metastasis. However, summing diameter overestimates actual tumor volume because volume is proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
2
10

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 39 publications
7
87
2
10
Order By: Relevance
“…These findings indicate a greater propensity of multifocal tumors to disseminate compared with unifocal ones and are in concordance with the results of Coombs and Boyages, 7 who also reported a statistically significant difference in the proportion of lymph nodepositive cases between unifocal and multifocal breast carcinomas (37.5% and 52.1%, respectively) as well as with the results of some other related studies. 5,6 LVI was clearly found to be associated with lymph node metastasis in the current study. These findings as well as the proportion of cases with LVI were comparable to the results in many other publications.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These findings indicate a greater propensity of multifocal tumors to disseminate compared with unifocal ones and are in concordance with the results of Coombs and Boyages, 7 who also reported a statistically significant difference in the proportion of lymph nodepositive cases between unifocal and multifocal breast carcinomas (37.5% and 52.1%, respectively) as well as with the results of some other related studies. 5,6 LVI was clearly found to be associated with lymph node metastasis in the current study. These findings as well as the proportion of cases with LVI were comparable to the results in many other publications.…”
Section: Discussionsupporting
confidence: 60%
“…Despite the well-recognized importance of the distribution of cancer within the breast for optimizing breast-conserving surgery, 4 there are conflicting results in the related literature regarding the significance of breast cancer multifocality, depending on the methodologic limitations and the various definitions used lacking a wide international consensus. [1][2][3][5][6][7][8][9][10][11][12][13][14] The diffuse growth pattern of some highly aggressive breast carcinomas 10 remains mainly unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…A major flaw is that, in cases of multifocality, the T stage indicates the largest invasive focus of the disease, but ignores the effective tumour burden, which may be significant if multiple foci are present. Our study accords with the findings of others in that the TNM system in its current form is not suitable for these purposes in the population of multifocal breast cancers [18,21,56,58]. We found that, despite the tumour being smaller, lymph node positivity was more prevalent among cancers containing multiple invasive foci, and a larger aggregate tumour burden involved a poorer outcome.…”
Section: Mode Of Detection Mammographic Appearance and Multifocalitysupporting
confidence: 91%
“…In general, multifocality is defined as the presence of two or more tumour foci separated by normal breast parenchyma. Some studies have attempted to analyze the association between the entire tumour burden and the outcome, by using the aggregate measure of the dimensions or volumes of the tumour foci [20,22,58,59]. These factors have been demonstrated as determinants of poorer characteristics and outcome [1,18,19,[21][22][23][24].…”
Section: Mode Of Detection Mammographic Appearance and Multifocalitymentioning
confidence: 99%
“…Most prior studies have predicted lymph node status by assessing the size and shape of lymph nodes [18][19][20][21]. Attempts at axillary staging by means of anatomical imaging of the axilla with CT or magnetic resonance imaging (MRI) have proved more useful than clinical examination [22].…”
Section: Introductionmentioning
confidence: 99%